Synthesis and characterization of dimethyltin(IV) complex with 2-methylpyridylbenzhydrazone (AcPyBzh): Crystal structure of [Me2SnCl (AcPyBzh)] - Affan, M.A; Ahmad, Fasihuddin Bin; Hitam, R.B; Shamsuddin, M.B; Yamin, Bohari Mohamad (2005)
The reaction of dimethyltin(IV) dihalide with 2-methylpyridylbenzhydrazone (AcPyBzh) afforded the complex compound [Me2SnCl(AcPyBzh)]. The complex was characterized by IR, 1H and 13C-{ 1H} NMR spectroscopic techniques and elemental analyses. The crystal structure of [Me2SnCL(AcPyBzh)] has been determined. The AcPyBzh anion in this complex acts as a monobasic NNO bidentate ligand, the tin(IV) lying in an elongated distrorted trigonal bipyramidal environment where the azomethine nitrogen and amidate oxygen, together with the two-methyl carbons, are in the equatorial plane, whereas the chloride is the apical ligand. The crystal is monoclinic, space group P2(I)/n, with a = 12.0945 (3), b = 7.5167 (2), c = 19.9795 (4) Å, α = 90°, β= 105.85°, γ = 90°.